Three kisses, one midnight eaudiobook A novel. - Chokshi, Roshani (Macmillan Young Listeners, 2022)
New York Times bestselling authors Roshani Chokshi, Evelyn Skye, and Sandhya Menon craft a spellbinding audiobook about discovering the magic of true love on one fateful, magical night in Three Kisses, One Midnight . The town of Moon Ridge was founded 400 years ago and everyone born and raised there knows the legend of the young woman who perished at the stroke of twelve that very same night, losing the life she was set to embark on with her dearest love. Every century since, one day a year, the Lady of Moon Ridge descends from the stars to walk among the townsfolk, conjuring an aura upon those willing to follow their hearts' desires. "To summon joy and love in another's soul For a connection that makes two people whole For laughter and a smile that one can never miss Sealed before midnight with a truehearted kiss." This year at Moon Ridge High, a group of friends known as The Coven will weave art, science, and magic during a masquerade ball unlike any other. Onny, True, and Ash believe everything is in alignment to bring them the affection, acceptance, and healing that can only come from romance—with a little help from Onny's grandmother's love potion. But nothing is as simple as it first seems. And as midnight approaches, The Coven learn that it will take more than a spell to recognize those who offer their love and to embrace all the magic that follows. A Macmillan Audio production from Wednesday Books.